2013
DOI: 10.1089/jmf.2012.0297
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of the Wild Edible Mushroom Lactarius salmonicolor

Abstract: The fruiting bodies of the edible mushroom Lactarius salmonicolor (Russulaceae) collected from the wild were extracted with solvents of increasing polarity and evaluated for their antioxidant capacity by 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging method. Additionally, their total phenolic content was evaluated by a modification of the Folin-Ciocalteu method. The methanol extract showed the most potent radical scavenging activity (inhibition of 36.7% of DPPH at 3 mg/mL and 6.8 mg gallic acid equiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 14 publications
0
14
1
7
Order By: Relevance
“…An azulene-type compound was identified in C. comatus. To our best knowledge, this compound has only been isolated previously in the mushroom of Lactarius salmonicolor [44]. DL-Menthol with strong inhibitory activity against fungi of Trichoderma [45] was also detected in the tested mushrooms.…”
Section: Volatile Compounds In Differentmentioning
confidence: 83%
“…An azulene-type compound was identified in C. comatus. To our best knowledge, this compound has only been isolated previously in the mushroom of Lactarius salmonicolor [44]. DL-Menthol with strong inhibitory activity against fungi of Trichoderma [45] was also detected in the tested mushrooms.…”
Section: Volatile Compounds In Differentmentioning
confidence: 83%
“…Previous studies revealed that compound 3 had no ORAC and lipid peroxide inhibiting property, but exhibited a slight effect in 2,2,1-diphenyl-1-picrylhydrazyl (DPPH) and superoxide dismutase (SOD)-like activity assays [27,28]. Wei et al investigated the antioxidant activity of compounds isolated from the medicinal mushroom Hericium erinaceus and experienced notable effects for cerevisterol (6) in the ORAC assay [29], while Athanasakis et al found moderate DPPH activity for 6 [30]. In another study cerevisterol (6) identified in the mycelia of H. erinaceus proved to possess considerable activity in the DPPH assay [31].…”
Section: Resultsmentioning
confidence: 99%
“…Lactarius deterrimus, an edible mushroom from the family Russulaceae, mainly grows in northern, northeastern and central Europe. Lactarius species represent a prospective source of natural immunostimulatory constituents with antitumor, antiviral and antimicrobial potential and activities [12,13].…”
Section: Introductionmentioning
confidence: 99%